(untitled) (Journal of Laboratory Animal Science, 2019)
In biomedical research, the use of laboratory animals is very vital and a critical part of effort to prevent, cure and treat a vast range of ailments. Globally around 50-100 million laboratory animals are used annually for experimentation. Rat, mouse, Guinea pig and rabbit are the most commonly used laboratory animals and among these, laboratory mouse is an important species. Variety of environmental factors can affect the outcomes of studies using laboratory rodents. One such factor is bedding. Physiological changes may occur after exposure to some types of bedding and could affect experimental results. Some bedding materials generate dust and particulates that might cause respiratory or ocular changes. Several new bedding materials have been introduced for laboratory rodents in the recent past, but there are only a few evaluation reports about their performance. In this study, we have compared the performance of different bedding materials like saw dust, paddy husk, corncob and paper shredding. We measured the micro-environment parameters like ammonia, sulfate, temperature, biomass changes, pH, moisture content, microbial load viz., total plate count, yeast and mold count, when housed on various types of bedding materials. We observed that the bedding materials have no significant effect on cage temperature, humidity and pH. The ammonia level in cages using corncob bedding (242 ± 3.65 mg/100g) was less when compared to all other beddings (Saw dust, 454 ± 2.4 mg/100g) and so prolong the interval between cage changing. The microbial monitoring also revealed less microbial load when corncob was used as bedding material. Hence, the present study suggests that corncob is more suitable as bedding material for housing laboratory mice.